A 3-CS Distributed Federated Transfer Learning Framework for Intelligent Edge Optical Networks - Yang, Hui; Yao, Qiuyan; Bao, Bowen; Li, Chao; Wang, Danshi; Zhang, Jie; Cheriet, Mohamed (Frontiers in Communications and Networks, 2021)
With the rapid development of optical network and edge computing, the operation efficiency of the edge optical network has become more and more important, requiring an intelligent approach to enhance the network performance. To enhance the intelligence of the edge optical network, this article firstly provides the demand for the development of edge optical networks. Then, a cross-scene, cross-spectrum, and cross-service (3-CS) architecture for edge optical networks is presented. Finally, a federated transfer learning (FTL) framework, realizing a distributed intelligence edge optical network, is proposed. The usability of the proposed framework is verified by simulation.